2014
DOI: 10.1590/s1519-38292014000200003
|View full text |Cite
|
Sign up to set email alerts
|

Classificação das mortes infantis em Belo Horizonte: utilização da lista atualizada de causas de mortes evitáveis por intervenções do Sistema Único de Saúde do Brasil

Abstract: Objetivos: analisar os óbitos de menores de um ano residentes em Belo Horizonte, segundo critérios de evitabilidadepropostos na Atualização da Lista de Causas de Mortes Evitáveis por Intervenção do Sistema Único de Saúde. Métodos: estudo descritivo que utilizou dados dos bancos dos Sistemas de Informação sobre Mortalidade e sobre Nascidos Vivos do Ministério da Saúde (DATASUS), no período de 2006 a 2011. As causas básicas de morte foram classificadas segundo critérios de evitabilidade. Foram calculados os co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
10
0
7

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 12 publications
(15 reference statements)
4
10
0
7
Order By: Relevance
“…For the triennia analyzed, there was a decreasing trend of preventable child deaths and an opposite situation regarding non-preventable deaths. Different behavior was found in a study conducted in Belo Horizonte (MG) in the period 2006-2011, which identified stable rates of non -preventable deaths, 31.2% in the first triennium and 31.3% in the second 27 .…”
Section: Discussionmentioning
confidence: 83%
“…For the triennia analyzed, there was a decreasing trend of preventable child deaths and an opposite situation regarding non-preventable deaths. Different behavior was found in a study conducted in Belo Horizonte (MG) in the period 2006-2011, which identified stable rates of non -preventable deaths, 31.2% in the first triennium and 31.3% in the second 27 .…”
Section: Discussionmentioning
confidence: 83%
“…There is a high under-five mortality rate in Brazil, and its reduction is a great challenge for these services. According to Menezes et al 10 , achieving this result depends on direct actions of public health policies, with improvement of primary health care services.…”
Section: Discussionmentioning
confidence: 99%
“…8 Os resultados deste estudo mostram que entre 8,0 e 10,0% dos óbitos ocorreram entre recém-nascidos com mais de 36 semanas e peso igual ou superior a 2.500 g e que essa proporção não foi estatisticamente diferente nos períodos analisados. Ou seja, em torno de 4 a 5% dos óbitos por sífilis poderiam ter sido evitados.…”
Section: Discussionunclassified
“…Ou seja, em torno de 4 a 5% dos óbitos por sífilis poderiam ter sido evitados. 8 Portanto, se ao longo do tempo examinado houvesse uma política eficiente e eficaz para a redução tanto da SC quanto da sífilis em gestantes, o percentual de óbitos nos recém-nascidos com as características mencionadas provavelmente seria muito menor ao final do período, em comparação ao início.…”
Section: Discussionunclassified